Epidemiological and virological findings during multiple outbreaks of equine influenza in South America in 2012. Issue 1 (January 2016) - Perglione, Cecilia Olguin; Gildea, Sarah; Rimondi, Agustina; Miño, Samuel; Vissani, Aldana; Carossino, Mariano; Cullinane, Ann; Barrandeguy, Maria
Abstract : Background: In 2012, equine influenza (EI) virus was confirmed as the cause of outbreaks of respiratory disease in horses throughout South America. In Uruguay and Argentina, hundreds of vaccinated thoroughbred horses in training and racing facilities were clinically affected. Objective: To characterise the EI viruses detected during the outbreak in Uruguay and Argentina. Methods: Virus was detected in nasopharyngeal swabs by a pan‐reactive influenza type A real‐time RT‐PCR. The nucleotide sequence of the HA1 gene was determined and analysed phylogenetically usingmega 5 software. Amino acid sequences alignments were constructed and virus was antigenically characterised with specific ferret antisera. Paired serum samples were tested by haemagglutination inhibition and single radial haemolysis. Results: The diagnosis of EIV was confirmed by real‐time RT‐PCR, virus isolation and serological testing. The phylogenetic analysis of HA1 gene sequences of 18 EI viruses indicated that all of them belong to clade 1 of the Florida sublineage of the American lineage and are closely related to viruses isolated in the United States in 2012. The HA1 of viruses identified in horses in racing facilities in Maroñas, Uruguay, and in Palermo, Argentina, displayed 100% amino acid sequence identity and were identical to that of a virus isolated in Dubai in 2012, from vaccinated endurance horses recently imported from Uruguay. Conclusions: The surveillance data reported illustrate the international spread of EI viruses and support the recommendations of the OIE expert surveillance panel to include viruses of the Florida sublineage in vaccines.